(untitled) (Window of Public Health Journal, 2026)
Low back pain is a common occupational health problem frequently experienced by workers and can reduce comfort, work capacity, and productivity. Loading and Unloading Workers (TKBM) are at high risk of low back pain because most of their work activities are manual, involving lifting and moving loads. This study aims to identify factors associated with low back pain complaints among TKBM workers, providing evidence-based insights for effective workplace health strategies. This study is quantitative and cross-sectional. The study population comprised 304 TKBM workers, and 168 respondents were selected using an accidental sampling technique. Data were collected using a questionnaire and analyzed using the Chi-Square test at a 95% confidence level (α = 0.05). The results showed that age, workload, length of service, and stretching habits had a significant relationship with complaints of low back pain. Meanwhile, body mass index (BMI) did not show a significant relationship with complaints of low back pain in TKBM workers. This study concluded that factors such as age, workload, length of service, and stretching habits play a role in the occurrence of complaints of low back pain in TKBM workers. Therefore, preventative measures are needed through workload management, regular stretching before work, and increasing worker awareness of the importance of maintaining musculoskeletal health to reduce the risk of lower back pain.